ECCE: Enhanced cooperative channel establishment for secure pair-wise communication in wireless sensor networks - Conti, Mauro; Di Pietro, Roberto; Mancini, Luigi V. (Ad hoc networks, 2007)
This paper presents the ECCE protocol, a new distributed, probabilistic, cooperative protocol to establish a secure pair-wise communication channel between any pair of sensors in a wireless sensor network (WSN). The main contributions of the ECCE protocol are: to allow the set-up of a secure channel between two sensors (principals) that do not share any pre-deployed key. This feature is obtained involving a set of sensors (cooperators) in the channel establishment protocol; to provide probabilistic authentication of the principals as well as the cooperators. In particular, the probability for the attacker to break authentication check decreases exponentially with the number of cooperators involved; to trade off the memory space required to store the pre-deployed encryption keys with the number of cooperators involved in the protocol. Hence, memory storage can be used to store keys built with the ECCE protocol, which helps amortizing the (limited) overhead incurred in the ECCE key set-up; to be adaptive to the level of threat the WSN is subject to. We provide analytical analysis and extensive simulations of ECCE, which show that the proposed solution increases both the probability of a secure channel set-up and the probability of channel resilience with respect to other protocols.